Ethanol Production from Hydrolyzed Kraft Pulp by Mono- and Co-Cultures of Yeasts: The Challenge of C6 and C5 Sugars Consumption - Rita H. R. Branco; Mariana S. T. Amândio; Luísa S. Serafim; Ana M. R. B. Xavier (Energies, 2020)
Second-generation bioethanol production’s main bottleneck is the need for a costly and technically difficult pretreatment due to the recalcitrance of lignocellulosic biomass (LCB). Chemical pulping can be considered as a LCB pretreatment since it removes lignin and targets hemicelluloses to some extent. Chemical pulps could be used to produce ethanol. The present study aimed to investigate the batch ethanol production from unbleached Kraft pulp of Eucalyptus globulus by separate hydrolysis and fermentation (SHF). Enzymatic hydrolysis of the pulp resulted in a glucose yield of 96.1 ± 3.6% and a xylose yield of 94.0 ± 7.1%. In an Erlenmeyer flask, fermentation of the hydrolysate using Saccharomyces cerevisiae showed better results than Scheffersomyces stipitis. At both the Erlenmeyer flask and bioreactor scale, co-cultures of S. cerevisiae and S. stipitis did not show significant improvements in the fermentation performance. The best result was provided by S. cerevisiae alone in a bioreactor, which fermented the Kraft pulp hydrolysate with an ethanol yield of 0.433 g·g−1 and a volumetric ethanol productivity of 0.733 g·L−1·h−1, and a maximum ethanol concentration of 19.24 g·L−1 was attained. Bioethanol production using the SHF of unbleached Kraft pulp of E. globulus provides a high yield and productivity.